1996
DOI: 10.1038/ki.1996.18
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of cell survival in cystic and dysplastic renal development

Abstract: Various aberrations of cell biology have been reported in polycystic kidney diseases and in cystic renal dysplasias. A common theme in these disorders is failure of maturation of renal cells which superficially resemble embryonic tissue. Apoptosis is a feature of normal murine nephrogenesis, where it has been implicated in morphogenesis, and fulminant apoptosis occurs in the small, cystic kidneys which develop in mice with null mutations of bcl-2. Therefore, we examined the location and extent of apoptosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
107
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 50 publications
9
107
1
Order By: Relevance
“…In the pcy kidney, abundant apoptotic cells were observed in the interstitium and occasionally in the cyst epithelium ( Figure 2D). These findings are consistent with the results of previous studies in other animal models of PKD as well as in human PKD (8,9).…”
Section: Tunelsupporting
confidence: 83%
See 3 more Smart Citations
“…In the pcy kidney, abundant apoptotic cells were observed in the interstitium and occasionally in the cyst epithelium ( Figure 2D). These findings are consistent with the results of previous studies in other animal models of PKD as well as in human PKD (8,9).…”
Section: Tunelsupporting
confidence: 83%
“…That JNK is not expressed in the normal immature kidney or in the epithelium of cysts in dysplastic kidneys suggests a role of JNK in differentiation at a later stage (4,6). Our study showed that the cyst epithelium of pcy mice has the same pattern of dysregulated MAPK expression as that of dysplasia and increased expression of PCNA and apoptosis in the cyst epithelium, a common feature of cystic diseases (7,8). Cyst epithelium in PKD is thought to have a persistent developmental phenotype as evidenced by altered expression of PAX2, vimentin, clusterin, Na ϩ /K ϩ -ATPase, and the EGF receptor (14).…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Increased levels of tubular cell apoptosis and proliferation are observed in human ADPKD (17)(18)(19), the cpk model of autosomal recessive PKD (19), the newly developed pck model of ADPKD (20), and dysplastic renal disease (21). Increased tubular cell apoptosis and proliferation are features of transgenic mice overexpressing the protooncogene c-myc (SBM mice) (22), mice lacking the transcription factor AP-2␤ (23), and Bcl-2-deficient mice (24).…”
Section: Discussionmentioning
confidence: 99%